PENGARUH TEPUNG GAPLEK DAN DEKSTRIN SEBAGAI EKSTENDER PEREKAT UREA FORMALDEHIDA TERHADAP KETEGUHAN REKAT KAYU LAPIS KAPUR - Adi Santoso1; Paribotro Sutigno2 (Jurnal Penelitian Hasil Hutan, 2004)
Urea formaldehyde resin is an adhesive for interior plywood manufacturing. Some materials can be added to the resin to reduce the glue utilization. This paper describes a study on the effect of extender addition to urea formaldehyde resin on the bonding strength of kapur (Dryobalanops sp.) plywood. This research used cassava flour and its dextrin as an extender with 3 percentage levels of extender i.e.: 10 %, 30%, and 50% based on weight of liquid resin. Each extender type has refinement of 100 and 200 mesh.The results showed that the effect of extender type on plywood bonding strength was not significant, while the percentage of extender has highly significant effect on the plywood bonding strength. The higher the extender percentage the lower the plywood bonding strength. Cassava flour 30% and its dextrin for extender meet the Japanese standard.